Anxiolytic, Promnesic, Anti-Acetylcholinesterase and Antioxidant Effects of Cotinine and 6-Hydroxy-L-Nicotine in Scopolamine-Induced Zebrafish (Danio rerio) Model of Alzheimer’s Disease - Boiangiu, Razvan Stefan (Antioxidants (Basel), 2021)
Cotinine (COT) and 6-hydroxy-L-nicotine (6HLN) are two nicotinic derivatives that possess cognitive-improving abilities and antioxidant properties in different rodent models of Alzheimer’s disease (AD), eluding the side-effects of nicotine (NIC), the parent molecule. In the current study, we evaluated the impact of COT and 6HLN on memory deterioration, anxiety, and oxidative stress in the scopolamine (SCOP)-induced zebrafish model of AD. For this, COT and 6HLN were acutely administered by immersion to zebrafish that were treated with SCOP before testing. The memory performances were assessed in Y-maze and object discrimination (NOR) tasks, while the anxiety-like behavior was evaluated in the novel tank diving test (NTT). The acetylcholinesterase (AChE) activity and oxidative stress were measured from brain samples. The RT-qPCR analysis was used to evaluate the npy, egr1, bdnf, and nrf2a gene expression. Our data indicated that both COT and 6HLN attenuated the SCOP-induced anxiety-like behavior and memory impairment and reduced the oxidative stress and AChE activity in the brain of zebrafish. Finally, RT-qPCR analysis indicated that COT and 6HLN increased the npy, egr1, bdnf, and nrf2a gene expression. Therefore, COT and 6HLN could be used as tools for improving AD conditions.